The p38 MAPK signalling pathway is required for glucose metabolism, lineage specification and embryo survival during mouse preimplantation development. (November 2015) - Sozen, Berna; Ozturk, Saffet; Yaba, Aylin; Demir, Necdet
Abstract: Preimplantation embryo development is an important and unique period and is strictly controlled. This period includes a series of critical events that are regulated by multiple signal-transduction pathways, all of which are crucial in the establishment of a viable pregnancy. The p38 mitogen-activated protein kinase (MAPK) signalling pathway is one of these pathways, and inhibition of its activity during preimplantation development has a deleterious effect. The molecular mechanisms underlying the deleterious effects of p38 MAPK suppression in early embryo development remain unknown. To investigate of the effect of p38 MAPK inhibition on late preimplantation stages in detail, we cultured 2-cell stage embryos in the presence of SB203580 for 48 h and analysed the 8-cell, morula, and blastocyst stages. We determined that prolonged inhibition of the p38 MAPK altered the expression levels of Glut1 and Glut4, decreased glucose uptake during the 8-cell to blastocyst transition, changed the expression levels of transcripts which will be important to lineage commitment, including Oct4/Pou5f1, Nanog, Sox2, and Gata6, and increased cell death in 8-16 cell stage embryos onwards. Strikingly, while the expression levels of Nanog, Gata6 and Oct4 / Pou5f1 mRNAs were significantly decreased, Sox2 mRNA was increased in SB203580-treated blastocysts. Taken together, our results provide important insight into the biological processes controlled by the p38 MAPK pathway and its critical role during preimplantation development. Highlights: Biological processes controlled by the p38 MAPK during preimplantation were studied. p38 MAPK signalling is required for proper expression of GLUT1 and GLUT4. Inhibition of p38 MAPK signalling affects lineage-specific transcription factor expression. Inhibition of p38 MAPK results in increased apoptosis in ICM layer.